Pharmaceutical patents and the right to health – Portugal and Brazil - Bahamonde Delgado, Ruben (2022)
The defence of the patent system's legitimacy, namely in the pharmaceutical field, is consolidated, although it is not exempt from criticism. Historically, when the patent law, a legal monopoly right, is confronted with the right of access to health, which inc ludes the right to the medicines necessary for its care, the mechanisms that have been established are scarce and weak. Nonetheless, one must recognize due merit in the search for a balance between the exclusive right of the holder of the legal monopoly and the right of the community to generalized access to medicines necessary to fulfil the right to health. In the current context of the covid-19 disease, where access to health care for all countries, rich and poor, is at stake, it seems that there is a greater will to make the right to health prevail over the property right of the holder of a pharmaceutical patent.